Crashworthiness design for trapezoid origami crash structure - Al-Jothery, H.K.M. (Universiti Malaysia Pahang, 2020)
Corrugations can be considered to be one of the ways to improve the mechanical properties of thin-walled structure in terms of manipulation of surface area. However, this theory requires further validation through experimentation of different materials. Although many research works have been done towards the corrugated shell structures, the flexibility of corrugated sheets of thermoset composite material remains unknown. This study focused on the effects of surface area manipulation by using trapezoid origami structure which is trapezoidal folded lobe shape on the absorbed energy and mechanical properties of Epoxy reinforced with S-type fibreglass. Then the trapezoidal folded lobe shape design was drawn by using AutoCAD which consist of the design of the corrugated composite sheets and the design of trapezoidal folded lobe shape mould. Moreover, the fabrication of the Aluminum mould was done by using a CNC milling machine according to the drawing. So, a compression moulding machine will be used to fabricate the composite structure. Therefore, the vibration and compression tests were carried out to perform a study on the behaviour of the trapezoidal folded lobe thermoset samples and to investigate their deformation behaviour respectively. Based on those tests, the results are shown that the trapezoidal origami samples have higher virtual stiffness than the flat samples, and the trapezoidal origami crash thin wall absorbs 40 more energy in Y-axis direction compared to in X-axis direction. Â© The Authors 2020.